2021
DOI: 10.1038/s41598-021-81038-5
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA expression profiles and associated ceRNA network analyses in epicardial adipose tissue of patients with coronary artery disease

Abstract: Epicardial adipose tissue (EAT) contributes to the pathophysiological process of coronary artery disease (CAD). The expression profiles of long non-coding RNAs (lncRNA) in EAT of patients with CAD have not been well characterized. We conducted high-throughput RNA sequencing to analyze the expression profiles of lncRNA in EAT of patients with CAD compared to patients without CAD. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses were executed to investigate the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…Indeed, several studies have shown that lncRNAs can act as ceRNAs that sequester miRNAs, thus allowing for de-repression of downstream miRNA targets ( Wang et al, 2019 ; Kang et al, 2021 ). Such integration between coding and non-coding RNA forms complex ceRNA networks that when dysregulated lead to cardiac remodeling after MI( Wang et al, 2021 ). We constructed a lncRNA-miRNA-mRNA ceRNA network and found that Mirt1 exhibited an obvious network hub feature, and the highest-degree microRNA related to Mirt1 was miR-466i-5p.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several studies have shown that lncRNAs can act as ceRNAs that sequester miRNAs, thus allowing for de-repression of downstream miRNA targets ( Wang et al, 2019 ; Kang et al, 2021 ). Such integration between coding and non-coding RNA forms complex ceRNA networks that when dysregulated lead to cardiac remodeling after MI( Wang et al, 2021 ). We constructed a lncRNA-miRNA-mRNA ceRNA network and found that Mirt1 exhibited an obvious network hub feature, and the highest-degree microRNA related to Mirt1 was miR-466i-5p.…”
Section: Discussionmentioning
confidence: 99%
“…Time-ordered ceRNA networks are constructed in ischemic and dilated cardiomyopathy (33). The ceRNA network controls inflammation through tanshinone IIA in atherosclerosis (34), affects metabolic and proinflammatory responses in coronary artery disease (CAD) (35), and regulates inflammation and cell proliferation in remote ischemic preconditioning of myocardial ischemia-reperfusion injury (36). NEAT1formed ceRNA participates in endothelial dysfunction by regulating inflammation in vein graft failure (37).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, there is increasing evidence that lncRNAs are able to affect the expression of protein-coding genes by competitively binding to shared miRNAs, which then reduces the degradation of protein-coding genes. Several studies have found that lncRNA-associated competing endogenous RNA cross-talks with cardiovascular disease pathogenetic processes [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%